Environmental impact and health of the bromide ion through the formation of carcinogenic compounds (Journal of the College of Basic Education, 2022)
The aim of this research is to study the environmental impact and health of bromide ion when it is present in the raw water source and concentrations higher than the allowable limit. As the bromide ion is oxidized by sterilization, as well as the help of other factors to bromine free, which in turn will react with organic materials composed of organic material brominated such as bromoform and acetic acid RETARDANTS and others that proved the studies and research over their serious impact on health and the environment through the illness of cancer when when its presence in of water. So our work to assess the concentrations of bromide ion in the source water resources (surface water) and over seven months of the year to see if you are within the permissible limits or not, where identified and U.S. Environmental Protection Agency maximum allowable amount (0.03 mg / L) if the water surface (collapsed) and by (38-33 mg/L) If the surface water (sea water) as well as we dealt with methods measured carbon total organic and calculate the expected DO compounds triglyceride Halomithan to determine the extent of displacement towards the vehicles Alambrmna when there is a bromide ion in water the source. We found already that the concentrations of bromide ion in raw water is higher than the allowable limit, and that is expected is formed from the chlorinated compounds within the limit Almsenouh it, which means that the removal of some carcinogenic compounds Alambrmna.